Gifted and talented children: Heterogeneity and individual differences - Pereira Da Costa, Maria; Lubart, Todd I. (Anales de Psicología / Annals of Psychology, 2016)
<span style="line-height: 115%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">The article tackles the topic that refers to giftedness beyond academic areas. Specifically, it focuses on musical talent. The work is differentiated into two parts. In the first part the authors expose the case of gifted students' heterogeneity. To do so, they present a previous research focused on the study of different patterns of response of gifted students to the WISC-IV. Such study illustrates the case of gifted students' diversity, showing that higher IQ students present higher inter-variability in their cognitive profiles. The second part of the article focuses on musical talent. In a first moment authors introduce the concept of musical talent and a literature review on the factors that influence that talent. From there, authors question if it could be possible to isolate the variables that differentiate the development of musical talent. To do so, Authors present a retrospective study based on interviews and questionnaires to parents and teacher of 42 non-gifted and 42 students identified as promising talent in music. The questionnaire assessed: Implication of parents, Motivation of the pupil, Work of the pupil and Contribution of the teacher. The authors are able to distinguish between developmental trends in the formation of musical talent, depending on children's age and styles on dealing with their musical assignments and work-load (experience music as a passion vs. as an obligation).